Duodenal Adenocarcinoma Is Characterized by Acidity, High Infiltration of Macrophage, and Activated Linc01559–GRSF1 Axis - Xinxin Huang; Ying Shi; Zekun Liu; Yihang Wu; Xiaotong Luo; Dongwen Chen; Zhengyu Wei; Chong Chen; Huaiqiang Ju; Xiaojian Wu; Xuanhui Liu; Zhanhong Chen; et al. (Biomedicines)
Background: Duodenal adenocarcinoma (DA) is often insidious due to the low rate of early diagnosis and because the mechanisms that underlie its malignant progression are poorly understood. The tumor microenvironment (TME) plays a crucial regulatory role in promoting tumor malignancy. Hence, this study aimed to identify novel biomarkers for early diagnosis and potential therapeutic targets for DA. Methods: Surgical resection samples and normal tissues from DA patients were collected for RNA sequencing (RNA-seq). The characteristics of TME in DA patients were analyzed, and the differentially expressed long non-coding RNAs (lncRNA) were screened. Functional experiments were performed to verify the relationship between Linc01559, G-rich sequence binding factor 1 (GRSF1), and tumor malignant phenotype. Results: The present study revealed that DA exhibits a significantly upregulated expression of acidic environment markers and a high degree of macrophage infiltration. Further investigation revealed that macrophages upregulate the expression of the long noncoding RNA, Linc01559, in DA through the STAT3/c-MYC signaling pathway, thereby promoting malignant phenotypes such as invasion, metastasis, tumor stemness, and apoptosis. The interaction between GRSF1 and Linc01559 was subsequently confirmed using RNA pulldown-mass spectrometry. It was further revealed that Linc01559 promotes the malignant phenotype of duodenal cancer cells through its interaction with GRSF1. Conclusions: These findings demonstrate that the acidic microenvironment influences the phenotype of DA by regulating the Linc01559–GRSF1 axis. Therefore, these findings provide potential targets for the early detection and treatment of DA.